A Survey on Strategic Competitive Position of Nepalese Banking Industries - Kayastha, Ram Krishna (PYC Nepal Journal of Management, 2010)
The paper examines strategic competitive position of the Nepalese banks using survey technique in Kathmandu valley. The total seventy questionnaires were collected out of one hundred and four questionnaires distributed to the manager level to officer level employees of the banks, i.e., 67 per cent responses rate. The paper finds that the most of banks have given emphasis to the nationwide branch networking and reliability/safety position, less important to the position of extra service and the staff advantage position respectively. It states that the number of branches of the banks will increase through out the nation. Similarly, the Nepalese commercial banks need to assure their customers regarding the greater safe banking position.